2017
DOI: 10.22146/veg.30900
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Pengayaan Oksigen dan Kalsium terhadap Pertumbuhan Akar dan Hasil Selada Keriting (<em>Lactuca sativa</em> L.) pada Hidroponik Rakit Apung

Abstract: Penelitian bertujuan untuk mengetahui pengaruh pengkayaan oksigen (O2) dankalsium (Ca) dalam larutan nutrisi hidroponik rakit apung terhadap pertumbuhan akar, hasil dan serapan Ca selada keriting. Penelitian dilaksanakan di Rumah KacaDepartemen Budidaya Pertanian, Fakultas Pertanian, Universitas Gadjah Mada yangterletak di Kecamatan Banguntapan, Kabupaten Bantul, Propinsi D.I. Yogyakarta, padabulan April-Juni 2016. Percobaan lapangan disusun dalam Rancangan Acak KelompokLengkap (RAKL) faktorial dengan tiga blo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
1
1
6

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 0 publications
1
1
1
6
Order By: Relevance
“…This mineral deposition symptom is also noted by Roosta et al (2016) when nutrient solution is aerated. However, this result is different from that reported by Krisna et al (2017) as calcium absorption in lettuce is higher in an aerated floating system than in non-aerated system. These differences suggested that there is still a room for further research and discussion.…”
Section: Some Chemical Contentscontrasting
confidence: 99%
See 1 more Smart Citation
“…This mineral deposition symptom is also noted by Roosta et al (2016) when nutrient solution is aerated. However, this result is different from that reported by Krisna et al (2017) as calcium absorption in lettuce is higher in an aerated floating system than in non-aerated system. These differences suggested that there is still a room for further research and discussion.…”
Section: Some Chemical Contentscontrasting
confidence: 99%
“…However, evidently the high difference of DO did not make a difference to the growth and yield of green lettuce. Goto et al (1996) reported the same results, that DO between 25-200% (of saturation) had no significant effect on yields of green lettuce, although this finding was contrast to the results reported by (Krisnawati, 2015) and (Krisna et al, 2017). This was presumably because plant roots mainly obtained oxygen from the air directly (above the nutrient solution), not just from dissolved oxygen in the nutrient solution.…”
Section: Plant Growthmentioning
confidence: 66%
“…Namun, suhu (Tabel 1) terlihat masih cukup tinggi dan kelembapan masih cukup rendah. Selada tumbuh optimal pada suhu udara 15-25 o C (Setyaningrum dan Saparinto, 2011) dengan kelembaban optimal yaitu 80-90 % (Krisna et al, 2017). Kebutuhan cahaya tanaman selada antara 200-400 footcandle (2152,78-4305,56 lux) (Setyaningrum dan Saparinto, 2011).…”
Section: Hasil Dan Pembahasan Iklim Mikrounclassified
“…Tinggi tanaman selada pada perlakuan tanpa naungan yaitu 23,59 cm nyata meningkat Tabel 1. Hasil pengukuran unsur-unsur iklim mikro tingkat naungan (Krisna et al, 2017).…”
Section: Tinggi Tanamanunclassified
See 1 more Smart Citation